Green Finance and Sustainable Development: A Cross-Sectional Study of Financial Mechanisms Driving Environmental Responsibility - Saeed Angorani (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
The purpose of this cross-sectional study is to investigate the complex connections that exist between environmental responsibility, sustainable development, and green financing mechanisms in financial institutions. The study employs quantitative approaches and cross-sectional analysis using a sample of 500 financial representatives to investigate connections between variables. To find patterns, statistical procedures including regression, t-test, and correlation are used. This research offers significant understanding of the complex relationships affecting environmental responsibility in the finance industry. The connections between green finance, innovation, CSR integration, and regulatory frameworks provide a thorough knowledge of the ways in which financial institutions may actively support sustainable development objectives.